Big data aggregation in disasters risk management systems. Issue 1 (May 2021) - Kovalenko, Oleksiy; Velev, Dimiter
Abstract: In the article the approach to aggregation of Big Data in the disasters risk management systems with using knowledge models is discussed. The basic concept is classifying and structuring the information received and stored in disasters management system using specific attributes of information, represented in the model of knowledge of disasters. We study the hierarchy of disasters risk management system and specificity of storing knowledge of disaster based on ontologies. Situation awareness is one of important elements in the complex problem of situation management. Disasters awareness is a phase of situational, or emergency, or crisis management in the case of disasters management.